'Five‐Session CAT' Consultancy: Using CAT to Guide Care Planning with People Diagnosed with Personality Disorder within Community Mental Health Teams. (10th August 2012) - Carradice, Angela
<x xml:space="preserve">Abstract</x> There are a number of clients that mental health teams (CMHTs) struggle to help. This group often have some form of personality disorder diagnosis. All workers can experience the client's presentation as challenging and this sometimes results in unhelpful repeated patterns between clients and services. Difficulties for this client group include abrupt state shifting, powerful dynamics, difficult/complex relationships with (often numerous) services, symptoms of dissociation, difficulties with emotional regulation and self abuse. Some people with these difficulties can present to services with a number of factors that mean it is hard to work helpfully with them such as having unstable and chaotic lives, experiencing significant ongoing risks from others and often coping day to day by using a variety of harmful strategies such as self‐harm, planning suicide and a significant amount of alcohol and/or drug use. The group of clients who experience these difficulties are often assessed as not being able to benefit from individual psychotherapy in the community. Five‐session cognitive analytic therapy (CAT) consultancy has been developed as a method to work jointly with mental health workers and their clients to develop a map to understanding their current difficulties, patterns of coping and to guide care planning. This paper describes the steps of 'five‐session CAT' consultancy and the skills involved. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Messages Newly evolved approach using CAT to help guide CMHT care planning For people with a diagnosis of personality disorder Who seem unsuitable for individual psychotherapy Because of the nature of their difficulties, mental health teams find such clients difficult to help